A novel mutation in the WFS1 gene identified in a Taiwanese family with low-frequency hearing impairment - Chung Shing-Fang; Wang Ying-Piao; Tsai Hsun-Tien; Lin Hung-Ching; Ho Guan-Min; Shu Min-Tsan (BMC, 2007)
Abstract Background Wolfram syndrome gene 1 (WFS1) accounts for most of the familial nonsyndromic low-frequency sensorineural hearing loss (LFSNHL) which is characterized by sensorineural hearing losses equal to and below 2000 Hz. The current study aimed to contribute to our understanding of the molecular basis of LFSNHL in an affected Taiwanese family. Methods The Taiwanese family with LFSNHL was phenotypically characterized using audiologic examination and pedigree analysis. Genetic characterization was performed by direct sequencing of WFS1 and mutation analysis. Results Pure tone audiometry confirmed that the family members affected with LFSNHL had a bilateral sensorineural hearing loss equal to or below 2000 Hz. The hearing loss threshold of the affected members showed no progression, a characteristic that was consistent with a mutation in the WFS1 gene located in the DFNA6/14/38 locus. Pedigree analysis showed a hereditarily autosomal dominant pattern characterized by a full penetrance. Among several polymorphisms, a missense mutation Y669H (2005T>C) in exon 8 of WFS1 was identified in members of a Taiwanese family diagnosed with LFSNHL but not in any of the control subjects. Conclusion We discovered a novel heterozygous missense mutation in exon 8 of WFS1 (i.e., Y669H) which is likely responsible for the LFSNHL phenotype in this particular Taiwanese family.